Assessment and development of flow boiling critical heat flux correlations for partially heated rectangular channels in different gravitational environments. (1st November 2022) - Darges, Steven J.; Devahdhanush, V.S.; Mudawar, Issam
Highlights: This study investigates flow boiling CHF in rectangular channels. Prior CHF correlations are assessed against data amassed in microgravity as well as at different flow orientations in terrestrial gravity. Assessment of correlations is segregated into subcooled, saturated, and two-phase inlet conditions. A new correlation is proposed, which is shown capable of predicting data for all three inlet conditions with high accuracy. Abstract: This study investigates critical heat flux (CHF) of n-Perfluorohexane flowing in a partially heated rectangular channel of 2.5-mm × 5.0-mm cross-section, within NASA's Flow Boiling and Condensation Experiment's (FBCE) Flow Boiling Module (FBM). A consolidated FBCE-CHF database is formed by compiling datasets from prior years of testing the FBM both at different orientations in Earth gravity (horizontal flow, vertical upflow, and vertical downflow) and on parabolic flights until it was launched to the International Space Station (ISS) in August 2021. This database encompasses a wide range of operating conditions (both subcooled liquid inlet of different inlet subcoolings and saturated two-phase inlet of different inlet qualities at different mass velocities and system pressures), heating configurations (single- and double-sided inlet), and different gravitational environments. The database is further categorized into three based on the type of CHF: subcooled CHF, saturated CHF with single-phase inlet, and saturated CHF with two-phase inlet. An exhaustive literature search is conducted to identify almost all flow boiling CHF correlations, which are then utilized to make predictions of the database and their accuracies assessed for each small subset of the database. Some correlations are capable of providing adequate CHF predictions for large portions of the database, while some provide very good predictions for very small subsets of operating conditions, typically those for which they were developed for. No single existing correlation is capable of predicting the entire database with good accuracy. Many correlations do not consider the effects of gravity on CHF, which is important for the different orientations tested, and even the few that do, are unsuccessful in predicting the microgravity data. A new simple CHF correlation is developed to address the drawbacks of the existing ones and is easy to use. This new correlation predicts the entire consolidated database with a mean absolute error of 17.44% with good accuracies for each subset of the database.